Experimental and computational evidence for xanthatin as a multi-target anti-cancer agent in ovarian cancer - Arshad, Hanzla; Afridi, Muhammad Shahbaz Khan (Bangladesh Journal of Pharmacology, 2025)
Xanthatin, a sesquiterpene lactone, was evaluated for its anti-cancer potential against SK-OV-3 ovarian cancer cells using both in vitro and in silico approaches. In vitro, xanthatin reduced cell viability, induced lactate dehydrogenase release, increased intracellular reactive oxygen species, and inhibited cell migration. The loss of mitochondrial mem-brane potential, activation of caspase-3 and caspase-9, and altered expression of BAX, CASPASE-3, and BCL-2 confirmed the induction of apoptosis. SwissADME and ProTox-II predicted favorable pharmacokinetic properties and safety profiles. Molecular docking suggested multi-target binding to tubulin, STAT3, VEGFR2, and topoisomerase II. These findings indicate that xanthatin exerts cytotoxic, pro-apoptotic, and anti-migratory effects by inducing oxidative stress and mitochondrial dysfunction. Therefore, xanthatin may represent a promising natural product lead for ovarian cancer therapy.